Hybrid use of the building as a method supporting epidemic safety - Rafał Janowicz; Wacław Szarejko; Marta Koperska-Kośmicka; Agnieszka Gębczyńska-Janowicz (Nofer Institute of Occupational Medicine, 2024)
The COVID-19 pandemic has resulted in changing organisational and technical requirements in the operation of treatment facilities. This paper summarises the available knowledge on the principles of hybrid design of the architecture of treatment units to ensure that different levels of sanitary and hygienic safeguards can be implemented. The basis of this narrative overview is an analysis of the existing Polish legislation on required personnel protection measures and the European Commission's recommendations for the long-term optimisation of building operating costs. In addition, due to the multifaceted and complex nature of the issue, the review was extended to include an example of practice in the technical adaptation of medical buildings for hybrid use in the event of a pandemic of an aetiological agent of risk category III, as a confirmation of the postulate regarding the need to modify the guidelines for the architectural design of the space of medical units, particularly those involved in the care of the elderly. Med Pr Work Health Saf. 2024;75(3):269-278